Cara Mudah Menghafal Al Qur’an Melalui Metode Tarjim Di Pondok Pesantren Tahfidzul Qur’ an Safinatul Huda III Bandung Diwek Jombang - Sunardi Kamaliyatul (Jurnal Pendidikan Islam, 2018)
Abstract: Everyone has their own method or method of memoriz ing. But the most widely used are those that are suitable and enjoyable for each individual. When examined, most methods suitable for each person are obtained through several attempts. The method or method of memorizing effective Al - Qur'an applies diversit y not uniformity. That is, between one person and another, the same method applies, depending on the character, absorption and memory of each. This method proved to be accurate for someone not necessarily accurate for others. The purpose of this study is t o investigate the implementation of the tarjim method, the supporting and inhibiting factors in memorizing the Qur'an. The application of the tarjim method is a foreign grammar study that emphasizes grammar analysis, vocabulary memorization, discourse tran slators, and writing exercises. This method emphasizes reading, writing and translation skills.